The Pto kinase mediates a signaling pathway leading to the oxidative burst in tomato - Chandra, Sreeganga (The National Academy of Sciences of the USA, 1996)
The Pto gene encodes a serine/threonine kinase that confers resistance in tomato to Pseudomonas syringae pv. tomato strains that express the avirulence gene avrPto. Partial characterization of the Pto signal transduction pathway and the availability of transgenic tomato lines (± Pto) make this an ideal system for exploring the molecular basis of disease resistance. In this paper, we test two transgenic tomato cell suspension cultures (±Pto) for production of H(2)O(2) following independent challenge with two strains of P. syringae pv. tomato (±avrPto). Only when Pto and avrPto are present in the corresponding organisms are two distinct phases of the oxidative burst seen, a rapid first burst followed by a slower and more prolonged second burst. In the remaining three plant–pathogen interactions, we observe either no burst or only a first burst, indicating that the second burst is correlated with disease resistance. Further support for this observation comes from the finding that both resistant and susceptible tomato lines produce the critical second oxidative burst when challenged with P. syringae pv. tabaci, a nonhost pathogen that elicits a hypersensitive response on both tomato lines. The Pto kinase is not required, however, for the oxidative burst initiated by non-specific elicitors such as oligogalacturonides or osmotic stress. A model describing a possible role for the Pto kinase in the overall scheme of oxidative burst signaling is proposed.